2018
DOI: 10.1111/aogs.13358
|View full text |Cite
|
Sign up to set email alerts
|

Prediction models for the risk of spontaneous preterm birth based on maternal characteristics: a systematic review and independent external validation

Abstract: IntroductionPrediction models may contribute to personalized risk‐based management of women at high risk of spontaneous preterm delivery. Although prediction models are published frequently, often with promising results, external validation generally is lacking. We performed a systematic review of prediction models for the risk of spontaneous preterm birth based on routine clinical parameters. Additionally, we externally validated and evaluated the clinical potential of the models.Material and methodsPredictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 41 publications
6
53
0
3
Order By: Relevance
“…Further, mothers with a history of smoking had higher risk for preterm births. Other studies have also shown similar associations for preterm births [4,[27][28][29]. Also, the risks were higher for mothers who did not use clean fuel.…”
Section: Discussionsupporting
confidence: 64%
“…Further, mothers with a history of smoking had higher risk for preterm births. Other studies have also shown similar associations for preterm births [4,[27][28][29]. Also, the risks were higher for mothers who did not use clean fuel.…”
Section: Discussionsupporting
confidence: 64%
“…The model has an AUC of 0.72 (95% CI 0.65-0.79). This is considered to be moderate and is comparable to prediction models from other clinical disciplines with an AUC range from 0.54 to 0.73 [22,23]. Bear in mind that the model is used for prediction of future events, compared to diagnostic models that estimate the probability of the presence or absence of an outcome in the present time.…”
Section: Discussionmentioning
confidence: 80%
“…To further improve the forecasting model, using the latest knowledge of the development model and potential risk factors, it is necessary to contribute to the personal risk assessment of spontaneous preterm delivery. (15)…”
Section: Discussionmentioning
confidence: 99%